Implementasi Pembelajaran PAI Berdiferensiasi Dalam Memenuhi Gaya Belajar Siswa SMP 1 Kamang Magek - Lavia, Sherly Sri; Karim, Hamdi Abdul; Afridona, Romy (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Differentiated learning is learning that provides independence to students learn using methods that are preferred and needed by each student. A teacher must realize that every child has a learning style and abilities are different from one another, so they cannot be sued to be able to achieve the same value in the same way. Teachers need to provide teaching methods that suit their individual needs. Therefore, differentiated learning also gives teachers independence modify the strategies and methods they will use in teaching. In its application, there are four aspects that teachers must know so that students can understand the lesson materials they study, namely the content aspects that contain teaching materials, aspects of the precess or activities that will be carried out by students when learning takes place in class, and assessment aspects in the form of making or producing products from the process has been given in learning, and the learning/1environment is very influential smoothness of the learning process.